Waters of the Exodus, Jewish Experiences with Water in Ptolemaic and Roman Egypt. - Nathalie LaCoste (Supplements to the Journal for the Study of Judaism, 2018)
In Waters of the Exodus , Nathalie LaCoste examines the Diasporic Jewish community in Ptolemaic and Roman Egypt and their relationship to the hydric environment. By focusing on four retellings of the exodus narrative composed by Egyptian Jews-Artapanus, Ezekiel the Tragedian, Wisdom of Solomon, and Philo of Alexandria-she lays out how the hydric environment of Egypt, and specifically the Nile river, shaped the transmission of the exodus story. Mapping these observations onto the physical landscape of Egypt provides a new perspective on the formation of Jewish communities in Egypt.